Microvascular decompression for elderly patients with trigeminal neuralgia. (July 2016) - Phan, Kevin; Rao, Prashanth J.; Dexter, Mark
Highlights: Microvascular decompression (MVD) is effective for trigeminal neuralgia (TN). The risks of MVD in elderly versus young patients is not clear. Our meta-analysis shows no difference in success rate. However elderly MVD patients had higher rates of death, stroke, thromboembolism. No differences were found for meningitis, nerve deficits and cerebrospinal fluid leak in elderly patients after MVD. Abstract: Microvascular decompression (MVD) has been demonstrated to be an excellent surgical treatment approach in younger patients with trigeminal neuralgia (TN). However, it is not clear whether there are additional morbidity and mortality risks for MVD in the elderly population. We performed a systematic literature review using six electronic databases for studies that compared outcomes for MVD for TN in elderly (cut-off ⩾60, 65, 70 years) versus younger populations. Outcomes examined included success rate, deaths, strokes, thromboembolism, meningitis, cranial nerve deficits and cerebrospinal fluid leaks. There were 1524 patients in the elderly cohort and 3488 patients in the younger cohort. There was no significant difference in success rates in elderly versus younger patients (87.5% versus 84.8%; P = 0.47). However, recurrence rates were lower in the elderly (11.9% versus 15.6%; P = 0.03). The number of deaths in the elderly cohort was higher (0.9% versus 0.1%; P = 0.003). Rates of stroke (2.5% versus 1%) and thromboembolism (1.1% versus 0%) were also higher for elderly TN patients. No differences were found for rates of meningitis, cranial nerve deficits or cerebrospinal fluid leak. MVD remains an effective and reasonable strategy in the elderly population. There is evidence to suggest that rates of complications such as death, stroke, and thromboembolism may be significantly higher in the elderly population. The presented results may be useful in the decision-making process for MVD in elderly patients with TN.